7.2 Adams - Sampling Of Toll PGE Concentrates At Impala Platinum Ltd (The Southern African Institute of Mining and Metallurgy, 2005)
EMMES Sampling Conference BACKGROUND & INTRODUCTION ?Impala acquires toll material to supplement production from ROM ?Toll material consists of filter cake, slurry and catalysts ?Samples are collected to determine the commercial values of the lots ?Slurry deliveries projected to remain relatively constant at 120tons dry solids per month, whereas filter cake deliveries set to increase five-fold to 800 tons dry solids per month ?Due to projected increase in toll material, new sampling and offloading facility presently under construction at Impala ?Presentation will cover two projects aimed at reducing the uncertainty associated with sampling of toll deliveries ?i.e. slurries and filter cake.